Becoming a midwife to wisdom: a retrospective account of practice of an action learning facilitator. (4th May 2019) - Scott, Daniel
ABSTRACT: In completing an action learning facilitation qualification in 2012, I documented an account of practice during the first year of my experience as a facilitator. The main areas of my learning related to four themes: fear of rejection, using and abusing power, content versus process and critical action learning. These learnings are linked to descriptions of five facilitation episodes during that formative first year, each surfacing a significant new challenge, question or realisation. Looking back seven years later, most of my early learnings about action learning facilitation (and myself) still resonate. With seven years' more experience, it is now the less visible aspects of the facilitator's role that seem more important and hold the most need for my continued learning.